The relationship of maternal glycemia to childhood obesity and metabolic dysfunction‡. (2nd January 2020) - Landon, Mark B.; Mele, Lisa; Varner, Michael W.; Casey, Brian M.; Reddy, Uma M.; Wapner, Ronald J.; Rouse, Dwight J.; Tita, Alan T. N.; Thorp, John M.; Chien, Edward K.; Saade, George; Grobman, William; et al.
Abstract: Objective: To determine the association of maternal glycemia with childhood obesity and metabolic dysfunction. Study design: Secondary analysis of follow-up data 5–10 years after a mild gestational diabetes mellitus (GDM) treatment trial. The relationship between maternal oral glucose tolerance testing (OGTT) at 24–31-week gestation and body mass index (BMI), fasting glucose, insulin, and anthropometric measurements (sum of skinfolds, subscapular/triceps ratio, and waist circumference) in the offspring of untreated mild GDM and non-GDM (abnormal 50-g screen/normal OGTT) women was assessed. Multivariable regression modeling controlling for maternal and neonatal characteristics was employed. Results: A cohort of 236 untreated mild GDM and 480 non-GDM offspring were analyzed. In the combined cohort, significant correlations existed between fasting, 1, 2, and 3 h maternal glucose and subscapular/triceps ratio (all p < .04) and in all OGTT values other than the 2-hour value for homeostatic model assessment-estimated insulin resistance (HOMA-IR) (all p < .04) and sum of skinfold measurements (all p < .03). No correlation was found between OGTT values and childhood BMI Z -score. Multivariable regression modeling showed that OGTT values were associated with only sum of skinfolds and subscapular/triceps ratio and not with childhood BMI Z -score. Hispanic ethnicity and prepregnancy maternal BMI were most consistently related to childhood BMI Z -score and HOMA-IR, and Hispanic ethnicity with fasting glucose. Conclusions: Among women with untreated mild GDM and those without GDM, maternal glycemia is associated with childhood anthropometric measures of obesity but not childhood BMI, fasting glucose, or insulin resistance. Hispanic ethnicity, maternal BMI, and gestational weight gain were consistently related to childhood BMI.